Comparative Studies of the (Anti) Mutagenicity of Baccharis dracunculifolia and Artepillin C by the Bacterial Reverse Mutation Test - Resende, Flavia Aparecida [UNESP]; Munari, Carla Carolina; Bentes Monteiro Neto, Moacir de Azevedo; Tavares, Denise Crispim; Bastos, Jairo Kenupp; da Silva Filho, Ademar Alves; Varanda, Eliana Aparecida [UNESP] (Mdpi Ag, 2012)
Baccharis dracunculifolia is a plant native from Brazil, commonly known as 'Alecrim-do-campo' and 'Vassoura' and used in alternative medicine for the treatment of inflammation, hepatic disorders and stomach ulcers. Previous studies reported that artepillin C (ArtC, 3-{4-hydroxy-3,5-di(3-methyl-2-butenyl)phenyl}-2(E)-propenoic acid), is the main compound of interest in the leaves. This study was undertaken to assess the mutagenic effect of the ethyl acetate extract of B. dracunculifolia leaves (Bd-EAE: 11.4-182.8 mu g/plate) and ArtC (0.69-10.99 mu g/plate) by the Ames test using Salmonella typhimurium strains TA98, TA97a, TA100 and TA102, and to compare the protective effects of Bd-EAE and ArtC against the mutagenicity of a variety of direct and indirect acting mutagens such as 4-nitro-O-phenylenediamine, sodium azide, mitomycin C, benzo[a]pyrene, aflatoxin B1, 2-aminoanthracene and 2-aminofluorene. The mutagenicity test showed that Bd-EAE and ArtC did not induce an increase in the number of revertant colonies indicating absence of mutagenic activity. ArtC showed a similar antimutagenic effect to that of Bd-EAE in some strains of S. typhimurium, demonstrating that the antimutagenic activity of Bd-EAE can be partially attributed to ArtC. The present results showed that the protective effect of whole plant extracts is due to the combined and synergistic effects of a complex mixture of phytochemicals, the total activity of which may result in health benefits.
Keywords: Baccharis dracunculifolia; artepillin C; Ames test; antimutagenicity; mutagenicity